Islamic Service Regulations for Optimizing Halal Tourism Potential in Pangandaran Based on The West Java Governor's Regulation and Halal Tourism Guidelines - Ahyani, Hisam; Naeli Mutmainah; Nurul Ilyana Muhd Adnan; Hasanah Abd Khafidz; Ending Solehudin; Miftakhul Huda; Agus Munjirin Mukhotib Lathif (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2024)
Pangandaran Regency holds considerable potential to emerge as a prominent halal tourism destination, supported by places of worship, halal cuisine, Islamic boarding school-based creative economies and halal accommodations. Despite these assets, the absence of specific regulations governing halal tourism hinders full optimization. Presently, Pangandaran relies on broader frameworks like West Java Governor Regulation Number 1 of 2022 on Sharia Economy and Finance Development, along with the 2019 West Java Halal Tourism Guidelines. This study explores the application of Islamic service ethics as a tailored regulatory approach to foster halal tourism growth in Pangandaran. It also aims to identify implementation challenges and propose viable solutions. The research uses qualitative methods to draw from regulatory analysis, interviews, questionnaires, observations, and documentation. The theoretical framework incorporates contemporary maqashid Sharia, legal change theory, maslahah mursalah, and halal theory. Findings reveal that integrating Islamic service ethics can effectively serve as a specialized regulation to unlock Pangandaran's halal tourism potential. This approach enhances security, comfort, and appeal for Muslim tourists, aligning with their religious values. Furthermore, the study underscores the broader economic benefits of halal tourism, offering a scalable regulatory model applicable to other regions with similar potential. The implications of this research extend to Islamic economics by promoting Sharia principles within the tourism sector, driving economic growth, and positioning Pangandaran as a leading halal tourism hub. This initiative bolsters local development and contributes to the overarching vision of integrated halal tourism in Indonesia.